(untitled) (MATEMATIKA, 2018)
This study presents a mathematical model examining wastewater pollutant removal through an oxidation pond treatment system. This model was developed to describe the reaction between microbe-based product mPHO (comprising Phototrophic bac- teria (PSB)), dissolved oxygen (DO) and pollutant namely chemical oxygen demand (COD). It consists of coupled advection-diusion-reaction equations for the microor- ganism (PSB), DO and pollutant (COD) concentrations, respectively. The coupling of these equations occurred due to the reactions between PSB, DO and COD to pro- duce harmless compounds. Since the model is nonlinear partial dierential equations (PDEs), coupled, and dynamic, computational algorithm with a specic numerical method, which is implicit Crank-Nicolson method, was employed to simulate the dy- namical behaviour of the system. Furthermore, numerical results revealed that the proposed model demonstrated high accuracy when compared to the experimental data. Keywords Oxidation pond; nonlinear PDEs; PSB; implicit Crank-Nicolson.